2019
DOI: 10.1002/ijc.31973
|View full text |Cite
|
Sign up to set email alerts
|

Demographic trends and KRAS/BRAFV600E mutations in colorectal cancer patients of South China: A single‐site report

Abstract: The incidence of colorectal cancer (CRC) is increasing in China. Here, we aimed to evaluate the latest demographic trends and KRAS/BRAF mutations status of Chinese CRC. Five thousand five hundred and forty-six CRC patients diagnosed from 2010 to 2017 were involved. KRAS exon 2 and BRAF V600E mutations were detected by Sanger sequencing and high-resolution melting analysis or allelic-specific probe method. Gene mutation profiles and clinicopathologic characteristics of 5495 patients were analyzed. The joinpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
6
17
0
Order By: Relevance
“…For the RCC and LCRC clinicopathological characteristics, our findings were similar to those in published data. RCC was more frequently associated with female patients, metastasis, mucinous, poorly-differentiated carcinoma, and a higher correspondence with the BRAF mutation and MSI-H status (Wangefjord et al, 2013;Li et al, 2015;Fu et al, 2019). Furthermore, our results showed that RCC was more common in younger patients who were under 50 years old, providing a diagnostic reference for clinicians.…”
Section: Discussionsupporting
confidence: 54%
“…For the RCC and LCRC clinicopathological characteristics, our findings were similar to those in published data. RCC was more frequently associated with female patients, metastasis, mucinous, poorly-differentiated carcinoma, and a higher correspondence with the BRAF mutation and MSI-H status (Wangefjord et al, 2013;Li et al, 2015;Fu et al, 2019). Furthermore, our results showed that RCC was more common in younger patients who were under 50 years old, providing a diagnostic reference for clinicians.…”
Section: Discussionsupporting
confidence: 54%
“…36 However, several studies showed that BRAF mutation was only found in 2.8-4.4% CRCs in Chinese population. 22,34 In our study, BRAF mutation presented in 3.4% (10/293) cases, which is accordant to the reported mutation rate in Chinese population. These results showed that there may exist a distinct nature of CRC between populations.…”
Section: Discussionsupporting
confidence: 90%
“…The missense mutations in KRAS occur in approximately 37.5-38% CRCs in Chinese populations. 22,34 A similar sequencing result was found in our cohort, in which KRAS mutation presented in 34.8% (96/276) patients with CRC. KRAS mutation has been found to be more likely to present in female, older patients, and tumors with right-side location, poor differentiation, elevated CEA or CA19-9, and high albumin/globular protein.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…ın our study population, the overall mutational rate for KRAS was 58.2%, which seemed to be higher to those reported for other populations. Fu X et al [6], found KRAS exon 2 mutation rates were 37.7% in 5546 CRC patients diagnosed from 2010 to 2017. guo F et al [7], KRAS exon 2 mutations were identified in 42.2% in 353 CRC patients from two Chinese clinical centers. Hamzehzadeh l et [8], detected mutations in exon 2 (codons 12 and 13) of the KRAS and NRAS genes using high resolution melting analysis, ıntplex design and Sanger sequencing in 87 ıranian CRC patients.…”
Section: Frequency Of Kras Mutations Among Patients With Crcmentioning
confidence: 99%